2019
DOI: 10.1186/s12913-019-4025-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the views of being a proxy from the perspective of unpaid carers and paid carers: developing a proxy version of the Adult Social Care Outcomes Toolkit (ASCOT)

Abstract: Background Outcomes-based policy and administration of public services present a compelling argument for the value of outcomes data. However, there are a number of challenges inherent in collecting these data from people who are unable to complete a paper-based survey or interview due to cognitive or communication impairments. In this paper, we explore the views of being a proxy from the perspective of unpaid carers and paid carers who may be asked to act as a proxy on behalf of the person(s) they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…This review identified relatively few measures developed specifically for proxy use, and several papers evaluating PROs adapted for proxy use. Adapted measures may be preferable in some cases given the goal of a proxy report substituting for an otherwise unavailable patient report; however, such adaptation will likely need to go beyond simple rewording and at a minimum clear instructions will likely be required [37]. Recently, the ISOQOL TCA-SIG developed good practices and process recommendations for translation and cultural adaptation of non-PRO clinical outcome assessments [34].…”
Section: Discussionmentioning
confidence: 99%
“…This review identified relatively few measures developed specifically for proxy use, and several papers evaluating PROs adapted for proxy use. Adapted measures may be preferable in some cases given the goal of a proxy report substituting for an otherwise unavailable patient report; however, such adaptation will likely need to go beyond simple rewording and at a minimum clear instructions will likely be required [37]. Recently, the ISOQOL TCA-SIG developed good practices and process recommendations for translation and cultural adaptation of non-PRO clinical outcome assessments [34].…”
Section: Discussionmentioning
confidence: 99%
“…These are 'proxy-patient' interviews, meaning that the proxy informant (staff or family) is being asked to internally reconstruct what the resident might think or feel about each domain. 303 It is therefore important that this interview is undertaken with a member of staff who knows the resident well. 303 Sometimes, the proxy will recognise that their view and the view of the resident differs.…”
Section: List Of Supplementary Materialsmentioning
confidence: 99%
“…303 It is therefore important that this interview is undertaken with a member of staff who knows the resident well. 303 Sometimes, the proxy will recognise that their view and the view of the resident differs. This is a wellestablished phenomenon in the literature and is why proxy interviews should be considered a different perspective from self-report 303 and is why we do not rely exclusively on this to inform our ratings.…”
Section: List Of Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…It's not okay if a person can't give a consent". IP1 therefore emphasised that proxies -who are responsible for answering questions on older adults' behalf, particularly regarding health and care services [3] -should be consulted before using ACMDs, "I would object strongly to any device being used without discussions with me and without my approval, because I speak for her [wife in residential care]". Both participants indicated that privacy decisions should be respectful.…”
Section: Using Acmds the Decision Is Older Adults' Toomentioning
confidence: 99%